When and Why of Mother Tongue Use in English Classrooms - Khati, Ashok Raj (Journal of NELTA, 2012)
It is often felt that teachers and students overuse their mother tongue, in this case, most probably the Nepali in English as a foreign language (EFL) classroom particularly in government-aided (Nepali medium) schools of Nepal. This, in result, minimizes the students’ exposure to English. This article starts with defining mother tongue. Then, it presents the use of mother tongue in EFL classroom in the global and Nepalese contexts followed by summary of three classroom observations and two focused group discussions among teachers and students studying at the secondary level. The final part of the paper presents some simple and applicable strategies and ways of enhancing English language use in the classroom on the part of students provided by three teachers’ trainers based on their experience. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6128 NELTA 2011; 16(1-2): 42-51